The Role of Lymph Node Metastasis in the Systemic Dissemination of Breast Cancer - Nathanson, S. David (Springer-Verlag, 2011)
BACKGROUND. Lymphatic invasion is necessary for regional lymph node (RLN) metastasis in breast cancer (BC), while systemic metastasis requires blood vessel (BV) invasion. The site of BV invasion could be at the primary BC site or through lymphovascular anastomoses. The vague pathologic term “lymphovascular invasion” (LVI) encourages the belief that peri/intratumoral BV invasion may be common. We investigated the relative contribution of RLN metastasis to systemic metastasis by studying the relationship among LVI and RLN and/or systemic metastasis in a population-based cohort of breast cancer patients. METHODS. Fisher’s exact test was done to assess global associations among LVI and RLN and/or systemic metastasis in a prospective database of breast cancer patients undergoing RLN biopsy. Logistic regression was used to determine multivariable contributions of LVI to metastasis when controlling for available demographic, radiologic, and pathologic variables. RESULTS. Of 1668 patients evaluated 25.4% were RLN positive and 10.4% had LVI. RLN metastasis was predicted by tumor size (P < .0001), HER-2/neu overexpression (P = .0022) and the interaction between LVI positive and HER-2/neu positive tumors (< .0001). Patients with LVI/HER-2-neu positive were 3 times as likely to have positive RLNs compared with patients LVI/HER-2-neu negative. Systemic metastasis was significantly (P = .0013) associated with LVI/ RLN positive, but not with LVI positive/RLN negative patients (P = .137). CONCLUSIONS. LVI predicted RLN metastasis. LVI also significantly predicted systemic metastasis, but only when the RLN was also positive. Since RLN requires lymphatic invasion, these data support the hypothesis that primary breast cancers often invade lymphatics to gain access to the systemic circulation.